2019
DOI: 10.34172/ajmb.2019.03
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Antibacterial Evaluation of Schiff Bases Derived FROM 2-Chloro-3-Quinolinecarboxaldehyde

Abstract: Background: Design, identification, and synthesis of new antimicrobial agents along with preventive proceedings are essential to confront antibiotic-resistant pathogenic bacteria. Heterocyclic Schiff bases are biologically important compounds whose antimicrobial potentials have been proven to bacterial and fungal pathogens. Objectives: In this study, some quinoline Schiff bases were synthesized from condensation of 2-chloro3-quinolinecarboxaldehyde and aniline derivatives. Their inhibitory activities were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…38 Also, quinoline based derivatives are considered structural components of many medicines with antibacterial, antimalarial, and anticancer properties. [36][37][38][39][40][41][42][43][44][45][46] Generally, quinolines are commonly used in many aspects such as the production of herbicides, corrosion inhibitors, and sensors. 36,47 In addition, aromatic compounds with nitro groups, especially nitroquinoline derivatives, are frequently used in the manufacture of drugs, dyes, and explosives.…”
Section: Introductionmentioning
confidence: 99%
“…38 Also, quinoline based derivatives are considered structural components of many medicines with antibacterial, antimalarial, and anticancer properties. [36][37][38][39][40][41][42][43][44][45][46] Generally, quinolines are commonly used in many aspects such as the production of herbicides, corrosion inhibitors, and sensors. 36,47 In addition, aromatic compounds with nitro groups, especially nitroquinoline derivatives, are frequently used in the manufacture of drugs, dyes, and explosives.…”
Section: Introductionmentioning
confidence: 99%
“…Quinolines are derivatives of pyridine and are found in many biologically active natural [ 5 , 6 ] and synthetic [ 7 , 8 , 9 ] compounds. Their Schiff base derivatives have also been identified with various pharmaceutical activities [ 10 , 11 ]. Although some free Schiff base ligands are known to be bioactive, literature has shown that incorporating metal in such ligands enhances their activities [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%